Optimisation of measuring system construction in the context of high flow variability - Gacek, Zbigniew; Jaworski, Jacek (Journal of natural gas science and engineering, 2020)
The article presents the concept of construction of natural gas measuring systems with high variability of gas flow through a metering station. The considerations are based on the analysis of the flow rate range of gas meters available on the European market, performance analysis of real measuring systems located in gas stations as well as on laboratory tests of gas meters. Studies were carried out and errors of turbine and rotary gas meter readings below their measuring ranges were presented. A concept of optimum construction of measuring systems utilised at stations with high gas flow variability was presented. A block diagram of the autonomous control of measuring strings was presented together with a microcontroller algorithm developed by the authors to support a system to control valves of the measuring strings. •Data on gas flow rates at measuring stations was analysed.•Metrological characteristics of turbine and rotor gas meters were tested in the range from the starting point to the Qmin.•A block diagram of the autonomous control of measuring strings was presented.